2007
DOI: 10.1093/jb/mvm191
|View full text |Cite
|
Sign up to set email alerts
|

Motor Deficits and Hyperactivity in Cerebral Cortex-specific Dyt1 Conditional Knockout Mice

Abstract: DYT1 dystonia is a primary generalized early-onset torsion dystonia caused by mutations in DYT1 that codes for torsinA and has an autosomal dominant inheritance pattern with approximately 30% penetrance. Abnormal activity in the pallidal-thalamic-cortical circuit, especially in the globus pallidus internus, is the proposed cause of dystonic symptoms. However, recent neuroimaging studies suggest significant contribution of the cerebral cortex. To understand the contribution of the cerebral cortex to dystonia, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
97
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(108 citation statements)
references
References 50 publications
7
97
1
3
Order By: Relevance
“…10,11 A conditional knockout mouse with selective torsinA deficits in the cerebral cortex had motor abnormalities reminiscent of dystonia, but no changes in striatal DA metabolism. 12 Similar inconsistencies have also been found in non-DYT1 experimental models of dystonia. [13][14][15][16] In the current study, we sought to identify changes in D 2 receptor availability linked to the presence of clinical manifestations in a cohort of DYT1 and DYT6 gene carriers.…”
supporting
confidence: 52%
“…10,11 A conditional knockout mouse with selective torsinA deficits in the cerebral cortex had motor abnormalities reminiscent of dystonia, but no changes in striatal DA metabolism. 12 Similar inconsistencies have also been found in non-DYT1 experimental models of dystonia. [13][14][15][16] In the current study, we sought to identify changes in D 2 receptor availability linked to the presence of clinical manifestations in a cohort of DYT1 and DYT6 gene carriers.…”
supporting
confidence: 52%
“…Dyt1 homozygous KO mice, Dyt1 ÁGAG heterozygous KI mice, paternally inherited Sgce heterozygous KO mice and Sgce homozygous KO mice were prepared and genotyped by PCR as described earlier (12,17,27,36 …”
Section: Micementioning
confidence: 99%
“…These findings suggest that torsinA is an essential protein for postnatal survival, and that ΔGAG is a loss of function mutation. In a more recent study, similar motor deficits were reported in a cortex-specific DYT1 knock-out model (Yokoi et al, 2008). The authors suggest that loss of torsinA in the cerebral cortex alone is sufficient to mimic behavioral deficits noticed in heterozygous ΔGAG knock-in and DYT1 knock-down mice.…”
Section: Animal Models Of Dyt1 Dystoniasupporting
confidence: 58%
“…Several murine models of DYT1 dystonia have been developed, and characterized to various degrees (Dang et al, 2005;Sharma et al, 2005;Shashidharan et al, 2005;Dang et al, 2006;Grundmann et al, 2007;Yokoi et al, 2008). These models include DYT1 knock-out , cortex-specific DYT1 knock-out (Yokoi et al, 2008), torsinA knock-down (Dang et al, 2006), transgenic overexpression of mutant and wild-type torsinA (Sharma et al, 2005;Shashidharan et al, 2005;Grundmann et al, 2007), and DYT1 ΔGAG knock-in (Dang et al, 2005; mouse models.…”
Section: Animal Models Of Dyt1 Dystoniamentioning
confidence: 99%
See 1 more Smart Citation